On the mechanisms and signature of atomic mechanisms in multiferroics: the example of Ba2 CoGe2O7 - Perez-Mato, J. M. (2011)
The systematic use of symmetry arguments, with inclusion of magnetic symmetry, is scarce in the investigation of magnetic materials. This is an unfortunate situation particularly when multiferroics are being studied. The lack of a consistent complete symmetry framework often prevents the distinction of what is the signature of a specific atomic mechanism and what is symmetryforced and therefore common to any possible underlying microscopic model. Here the recently reported magnetoelectric properties of Ba2CoGe2O7 [Murakawa et al. (2010). Phys. Rev. Lett. 105, 137202] are discussed as an extreme example of this situation, and it is shown how three of the four magnetoelectric responses that have been reported for this compound can be predicted by symmetry considerations without appealing to any specific atomic mechanism.